Avaliação da atividade antibacteriana e sinérgica da curcumina com oxacilina e vancomicina frente a cepas de Staphylococcus aureus sensíveis e resistentes a meticilina (MRSA), e análise do seu mecanismo de ação - Nogueira, Lavouisier Frankilin Brito (2019)
Staphylococcus aureus was the first isolated microorganism to be resistant to antimicrobials, taking a short time to exhibit resistance to penicillin G, and later to methicillin a β-lactamic less sensitive to penicillinases. These strains are now known as methicillin resistant Staphylococcus aureus (MRSA). Currently, in Latin America, approximately 45% of bacteremia cases caused by S. aureus are related to MRSA strains. These infections lead to increased cost and length of stay, making these microorganisms a worldwide public health problem. Thus, the search for new compounds for the development of new therapeutic options is necessary and urgent. Curcumin, a natural product traditionally used in Indian culture as a spice, has been pointed out in several studies as an anti-cancer, anti-inflammatory and healing compound and among other functions as antimicrobial. Having been reported by some researchers its activity against S. aureus. The aim of this work was to evaluate curcumin activity against methicillin sensitive and resistant S. aureus strains by broth microdilution techniques and flow cytometry. Curcumin showed antibacterial activity on the 8 sensitive strains and on the 13 resistant strains tested, with minimum inhibitory concentration (MIC) ranging from 125 - 500 µg / mL. It also showed synergistic activity in combination with oxacillin in 53.8% of the strains tested. And in 15.3% of the strains tested with vancomycin, in the synergism tests curcumin did not induce an antagonistic effect in any of the tested strains, for any of the evaluated combinations. In flow cytometry tests, curcumin was able to cause increased membrane permeability to propidium iodide (PI), and DNA fragmentation, as evidenced by the TUNEL test for all concentrations tested. Thus, it can be concluded that curcumin is capable of inhibiting the in vitro proliferation of methicillin sensitive and resistant S. aureus strains and has no negative effects in combination with the tested antimicrobial drugs, thus demonstrating its ability to act as a possible antibacterial agent with apoptotic action.